Processing method of sugar-thinning metal surface
By combining roughening the metal surface and spraying hydrophobic silica powder and lubricating oil, the existing coating technology has poor durability under high temperature conditions, and efficient sugar-repellent effect and lubricating performance are achieved.
Patent Information
- Application Number
- CN202510718317.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-01
AI Technical Summary
The existing coating technology has poor durability under high temperature conditions, is high in cost or is prone to brittle cracking, making it difficult to effectively reduce the adhesion of food ingredients on the metal surface.
By roughening the metal surface, hydrophobic silica powder is sprayed and lubricating oil is applied thereon, forming a combination of the rough surface and the silica layer, thereby improving the thermal stability and sugar repellency of the lubricating oil.
Significantly reduce the adhesion of sugar substances on the surface of the equipment, improve cleaning efficiency and service life, and ensure the stability and durability of lubricating oil in high temperature environments.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anti-sticking in food processing, and particularly to a processing method for a sugar-repellent metal surface. Background Art
[0002] In the food processing industry, one of the goals of surface treatment technology is to reduce the adhesion of food components, especially anti-sticking under high-temperature and long-term use conditions. Existing coating technologies such as polytetrafluoroethylene (PTFE), silicone oil coatings, and ceramic coatings can reduce adhesion to a certain extent and improve the cleaning efficiency of equipment, but each of these methods has its limitations. PTFE and silicone oil coatings are prone to degradation under high-temperature conditions and have poor durability, while ceramic coatings, although wear-resistant and chemically resistant, have relatively high costs and may crack when subjected to impact. The above problems need to be solved urgently. Summary of the Invention
[0003] The present invention discloses a processing method for a sugar-repellent metal surface, aiming to solve the technical problems existing in the prior art.
[0004] The present invention adopts the following technical solutions:
[0005] The present invention provides a processing method for a sugar-repellent metal surface, which includes the following steps:
[0006] Process the metal surface to form a rough surface;
[0007] Hydrophobically treat the silica powder;
[0008] Spray the hydrophobically treated silica powder onto the metal surface to form a silica layer;
[0009] Coat lubricating oil on the surface of the silica layer to form a lubricating oil layer, and the processing is completed.
[0010] In the processing method for the sugar-repellent metal surface of the present invention, the viscosity of the lubricating oil is 50 CS - 150 CS.
[0011] In the processing method for the sugar-repellent metal surface of the present invention, the viscosity of the lubricating oil is 100 CS.
[0012] In the processing method for the sugar-repellent metal surface of the present invention, the particle size of the silica powder is greater than or equal to 10 nm and less than or equal to 100 nm.
[0013] In the processing method for the sugar-repellent metal surface of the present invention, the particle size of the silica powder is 30 nm.
[0014] In the processing method for the sugar-repellent metal surface of the present invention, the thickness of the silica layer is greater than or equal to 1 μm and less than or equal to 5 μm.
[0015] In the processing method of the sugar-repellent metal surface of the present invention, the thickness of the silica layer is 2 μm.
[0016] In the processing method of the sugar-repellent metal surface of the present invention, the process of spraying the silica powder after hydrophobic treatment onto the metal surface is carried out under heating conditions, and the heating temperature of the metal is 60 - 80 °C.
[0017] In the processing method of the sugar-repellent metal surface of the present invention, after applying lubricating oil on the surface of the silica layer, it is placed in an environment with an ambient temperature of 20 °C - 25 °C and a relative humidity of 40% - 60% and hung until no lubricating oil drips.
[0018] In the processing method of the sugar-repellent metal surface of the present invention, the ambient temperature is 25 °C and the relative humidity is 40%.
[0019] In the processing method of the sugar-repellent metal surface of the present invention, the lubricating oil is 3H food-grade dimethyl silicone oil or food-grade PFPE lubricating oil or food-grade vegetable oil or food-grade synthetic ester lubricating oil or food-grade white mineral oil.
[0020] In the processing method of the sugar-repellent metal surface of the present invention, the step of processing the metal surface to form a rough surface is carried out using a laser. After processing, the sample is soaked in a mixed solution of hydrochloric acid and oxalic acid to remove the carbonized layer.
[0021] In the processing method of the sugar-repellent metal surface of the present invention, the step of processing the metal surface to form a rough surface is achieved by laser processing; the power of the laser is 500 mW - 1 W, the scanning speed is 2 mm / s - 5 mm / s; the scanning line spacing is 100 μm - 200 μm.
[0022] The technical solution adopted by the present invention can achieve the following beneficial effects:
[0023] The present invention mainly provides a processing method for the sugar-repellent metal surface. By processing the metal surface to form a rough surface, spraying silica powder on the rough surface, and finally applying lubricating oil on the formed silica layer; through the cooperation of the rough surface and the silica layer, the thermal stability of the lubricating oil can be improved, thereby avoiding the problem of rapid degradation caused by direct exposure to high-temperature environments, improving durability, ensuring the lubricating and anti-sticking properties of the lubricating oil, and being able to improve the sugar-repellency of the surface, reduce the sliding angle, and increase the contact angle. Detailed Embodiments
[0024] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. In the description of the present invention, it should be noted that the term "or" is generally used in the sense of including "and / or", unless the content clearly indicates otherwise.
[0025] Unless explicitly indicated to the contrary, the numerical parameters in this specification and the appended claims can be approximate values, which can be changed according to the required characteristics obtained through the content of the present invention. Specifically, all the numbers representing the contents of components, reaction conditions, etc. used in the specification and claims should be understood to be modified by the term "about" in all cases. Generally, the meaning expressed is that it includes a change of ±10% in some embodiments, a change of ±5% in some embodiments, a change of ±1% in some embodiments, and a change of ±0.5% in some embodiments for a specific quantity.
[0026] Furthermore, the word "comprising" does not exclude the presence of materials or steps not listed in the claims. Ordinal numbers such as "first", "second", "third" and Arabic numerals, letters, etc. used in the specification and claims to modify corresponding elements or steps do not themselves imply an order in the manufacturing method, and the use of these ordinal numbers is only used to clearly distinguish the steps.
[0027] In addition, unless the steps are specifically described or must occur in sequence, the order of the above steps is not limited to the above-listed order and can be changed or rearranged according to the required design. And the above embodiments can be mixed and used with each other or mixed and used with other embodiments based on considerations of design and reliability, that is, the technical features in different embodiments can be freely combined to form more embodiments.
[0028] Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.
[0029] To solve the problems existing in the prior art, an embodiment of the present application provides a processing method for a sugar-repellent metal surface.
[0030] A processing method for a sugar-repellent metal surface, which comprises the following steps:
[0031] Step S1, processing the metal surface to form a rough surface;
[0032] Step S2, performing a hydrophobic treatment on the silica powder;
[0033] Step S3: Spray the hydrophobically treated silica powder onto the metal surface to form a silica layer;
[0034] Step S4: Coat lubricating oil on the surface of the silica layer to form a lubricating oil layer, and the processing is completed.
[0035] A processing method for a sugar-repellent metal surface according to the present invention forms a rough surface by processing the metal surface, sprays silica powder on the rough surface, and finally coats lubricating oil on the formed silica layer; through the cooperation of the rough surface and the silica layer, the thermal stability of the lubricating oil can be improved, thereby avoiding the problem of rapid degradation caused by direct exposure to high-temperature environments, improving durability, ensuring the lubricating and anti-sticking properties of the lubricating oil, and being able to improve the sugar-repellent property of the surface, reduce the sliding angle, and increase the contact angle; the sliding angle of the treated surface with respect to sugar substances (such as syrup, honey, maltose) is less than 10°, significantly reducing the adhesion of sugar to the equipment surface, and improving the cleaning efficiency and service life.
[0036] In some preferred embodiments, in step S4, the viscosity of the lubricating oil is 50 CS - 150 CS; when the viscosity of the lubricating oil is too high, the fluidity is poor, and it is difficult to evenly spread on the metal surface to form a continuous protective film, resulting in uneven sugar-repellent effects and reduced adhesion to the metal surface, reducing the sugar-repellent performance; when the viscosity is too low, the adhesion of the lubricating oil to the metal surface is poor, it is easy to flow away, the sugar-repellent effect is unstable, and the durability is poor.
[0037] Preferably, the viscosity of the lubricating oil is 100 CS.
[0038] In some preferred embodiments, the particle size of the silica powder is greater than or equal to 10 nm and less than or equal to 100 nm; within this range, a stable and uniform silica layer can be formed on the metal surface, improving the sugar-repellent property, durability, and hydrophobicity. If the particle size is too large or too small, the sugar-repellent performance, hydrophobic performance, and durability will all decrease.
[0039] Preferably, the particle size of the silica powder is 30 nm.
[0040] In some preferred embodiments, the thickness of the silica layer is greater than or equal to 1 μm and less than or equal to 5 μm; if the coating is too thick, it will affect the performance of the metal material itself, and the sugar-repellent property and durability will become worse; if the coating is too thin, the sugar-repellent property and durability will also become worse.
[0041] Preferably, the thickness of the silica layer is 2 μm.
[0042] Preferably, the silica is food-grade silica.
[0043] In some preferred embodiments, the process of spraying the hydrophobic-treated silica powder onto the metal surface is carried out under heating conditions, and the heating temperature of the metal is 60 - 80°C; thereby, the film-forming speed of the silica powder is increased. Specifically, 0.3 g of the treated hydrophobic silica powder is dissolved in 30 ml of absolute ethanol and ultrasonically treated for ten minutes to make it uniformly mixed, and the ultrasonically treated solution is evenly sprayed onto the surface of the sample with a spray gun.
[0044] In some preferred embodiments, after applying the lubricating oil on the surface of the silica layer, it is placed in an environment with an ambient temperature of 20°C - 25°C and a relative humidity of 40% - 60% and hung until no lubricating oil drips, so as to ensure that the lubricating oil is evenly distributed on the surface; too high temperature and relative humidity will cause the formed lubricating oil layer to be too thin, affecting durability, and easily cause the lubricating oil to deteriorate and affect the oil repellency; too low temperature and relative humidity will increase the viscosity of the silicone oil. When the temperature is too low, the lubricating oil may become too viscous and its fluidity will be significantly reduced; the lubricating oil itself has a certain degree of hydrophobicity, but in a low-humidity environment, a small amount of moisture may still be adsorbed on the surface of the lubricating oil. When the temperature is too low, the adsorbed moisture may freeze, thus affecting the performance of the lubricating oil.
[0045] Preferably, the ambient temperature is 25°C and the relative humidity is 40%.
[0046] In some preferred embodiments, the lubricating oil is 3H food-grade dimethyl silicone oil and / or food-grade PFPE lubricating oil and / or food-grade vegetable oil and / or food-grade synthetic ester lubricating oil and / or food-grade white mineral oil. Preferably, the lubricating oil is dimethyl silicone oil.
[0047] In some preferred embodiments, the step of processing the metal surface to form a rough surface is carried out using a laser. After processing, the sample is soaked in a mixed solution of hydrochloric acid and oxalic acid to remove the carbonized layer; preferably, the volume ratio of hydrochloric acid to oxalic acid is 2:1 to 5:1; the optimal ratio is 3:1.
[0048] Preferably, after the step of removing the carbonized layer, it further includes a step of ultrasonically treating the rough surface.
[0049] Preferably, the step of ultrasonically treating the rough surface includes:
[0050] Put the metal surface into a mixed solution of absolute ethanol and acetone for ultrasonic cleaning for 5 - 15 minutes, then rinse with deionized water, and then dry until completely dry.
[0051] Preferably, the metal surface is ultrasonically cleaned with absolute ethanol for 10 minutes; the volume ratio of absolute ethanol to acetone is 1:1.
[0052] In some preferred embodiments, it further includes a step of cleaning the surface to be processed of the metal.
[0053] Specifically, the steps for cleaning the surface of the metal to be processed include: ultrasonically cleaning with acetone in an ultrasonic cleaner for 15 minutes to remove most of the organic pollutants; ultrasonically cleaning with absolute ethanol to further remove the remaining organic substances and some inorganic salts; ultrasonically cleaning with deionized water to thoroughly remove any residual chemical substances and particles, and after the cleaning is completed, placing it in a blast drying oven for drying.
[0054] In some preferred embodiments, the hydrophobic modification of silica can adopt the modification methods in the prior art, which are not limited herein.
[0055] Preferably, the hydrophobic modification of silica includes the following steps:
[0056] 1. Immerse the 100 nm silica powder successively in 5% dilute hydrochloric acid and deionized water and ultrasonically clean for 30 minutes to remove surface impurities and activate the hydroxyl groups, and then dry at 100 °C for 2 hours.
[0057] 2. Preparation of the fluorosilane solution: Dissolve 3% (by mass) of heptadecafluorodecyltrimethoxysilane (purity ≥ 98%) in absolute ethanol, add 1 vol% of deionized water for catalytic hydrolysis, and stir for 30 minutes until the solution is clear.
[0058] 3. Mix the pretreated silica powder and the fluorosilane solution at a solid-liquid ratio of 1:10, stir at a constant temperature of 50 °C for 2 hours to cause the silanol groups (Si–OH) generated by the hydrolysis of the silane to condense with the surface hydroxyl groups of the silica to form covalent bonds (Si–O–Si). Then, centrifuge at 8000 rpm for 5 minutes, dry the centrifuged product in an oven at 60 °C for 12 hours, and finally grind to obtain the hydrophobic modified SiO2 nanoparticles.
[0059] In some preferred embodiments, the step of processing the metal surface to form a rough surface is achieved by laser processing; the power of the laser is 500 mW - 1 W, the scanning speed is 2 mm / s - 5 mm / s; the scanning line spacing is 100 μm - 200 μm, that is, a reticular scanning line is formed. Preferably, the power of the laser is 800 mW, the scanning speed is 5 mm / s; the scanning line spacing is 100 μm.
[0060] Example 1
[0061] Taking the hydrophobic sugar processing of the stainless steel surface as an example, the processing steps are as follows:
[0062] Step S1, process the stainless - steel surface to form a rough surface. The processing parameters are: the power of the laser is 800 mW, the scanning speed is 5 mm / s; the scanning line spacing is 100 μm; after processing, perform decarburization, ultrasonic cleaning with acetone, ultrasonic cleaning with absolute ethanol, and ultrasonic cleaning with deionized water on the processed surface;
[0063] Step S2, perform hydrophobic treatment on the silica powder. The particle size of the silica powder after hydrophobic treatment is 30 nm;
[0064] Step S3, spray the hydrophobic - treated silica powder onto the stainless - steel surface to form a silica layer with a thickness of 2 μm;
[0065] Step S4, coat the surface of the silica layer with lubricating oil. The viscosity of the lubricating oil is 100 CS, and hang it until no lubricating oil drips, forming a lubricating oil layer, and the processing is completed.
[0066] After testing, the contact angle of the finally sugar - repellent - modified stainless - steel surface is 108.68°, the sliding angle is 2.9°, and the durability is 99.76°.
[0067] Among them, the durability is verified by the change of the contact angle after sand - paper polishing the coating. First, prepare a coating sample, use 800 - mesh sandpaper to quantitatively polish the sample under a constant pressure to simulate the actual wear condition. After polishing, ultrasonically clean and dry the surface with ethanol to remove the interference of grinding debris. Use a contact - angle measuring instrument to select 5 sites in the central area of the sample, measure the contact angles of 3 - 5 μL of maltose and honey and take the average value, and compare the data before and after wear. The one with a smaller difference in contact angle before and after testing is better.
[0068] Example 2
[0069] The difference between this example and Example 1 is that the power of the laser is 500 mW, the scanning speed is 2 mm / s; the scanning line spacing is 100 μm, and the other steps are the same as in Example 1.
[0070] After testing, the contact angle of the finally sugar - repellent - modified stainless - steel surface is 104.6°, the sliding angle is 4.5°, and the durability is 94.21°.
[0071] Example 3
[0072] The difference between this example and Example 1 is that the power of the laser is 1 W, the scanning speed is 5 mm / s; the scanning line spacing is 200 μm, and the other steps are the same as in Example 1.
[0073] After testing, the contact angle of the finally sugar - repellent - modified stainless - steel surface is 105.35°, the sliding angle is 4°, and the durability is 94.16°.
[0074] Example 4
[0075] The difference between this embodiment and Embodiment 1 is that the particle size of the silica powder after the hydrophobic treatment is 10 nm, and the remaining steps are the same as those in Embodiment 1.
[0076] After testing, the contact angle of the finally sugar-repellent modified stainless steel surface is 101.7°, the sliding angle is 5.1°, and the durability is 92.1°.
[0077] Embodiment 5
[0078] The difference between this embodiment and Embodiment 1 is that the particle size of the silica powder after the hydrophobic treatment is 100 nm, and the remaining steps are the same as those in Embodiment 1.
[0079] After testing, the contact angle of the finally sugar-repellent modified stainless steel surface is 102.52°, the sliding angle is 4.35°, and the durability is 93.52°.
[0080] Embodiment 6
[0081] The difference between this embodiment and Embodiment 1 is that the thickness of the silica layer formed in step S3 is 1 μm, and the remaining steps are the same as those in Embodiment 1.
[0082] After testing, the contact angle of the finally sugar-repellent modified stainless steel surface is 105.4°, the sliding angle is 4.2°, and the durability is 95.3°.
[0083] Embodiment 7
[0084] The difference between this embodiment and Embodiment 1 is that the thickness of the silica layer formed in step S3 is 5 μm, and the remaining steps are the same as those in Embodiment 1.
[0085] After testing, the contact angle of the finally sugar-repellent modified stainless steel surface is 107.76°, the sliding angle is 3.7°, and the durability is 96.42°.
[0086] Embodiment 8
[0087] The difference between this embodiment and Embodiment 1 is that the viscosity of the lubricating oil in step S4 is 50 CS, and the remaining steps are the same as those in Embodiment 1.
[0088] After testing, the contact angle of the finally sugar-repellent modified stainless steel surface is 105.8°, the sliding angle is 4.5°, and the durability is 95.4°.
[0089] Embodiment 9
[0090] The difference between this embodiment and Embodiment 1 is that the viscosity of the lubricating oil in step S4 is 150 CS, and the remaining steps are the same as those in Embodiment 1.
[0091] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 107°, the sliding angle is 3.3°, and the durability is 96.82°.
[0092] Comparative Example 1
[0093] The difference between this comparative example and Example 1 is that the particle size of the silica powder after the hydrophobic treatment in Step S2 is 5 nm, and the other steps are the same as those in Example 1.
[0094] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 106.23°, the sliding angle is 3.9°, and the durability is 95.92°.
[0095] Comparative Example 2
[0096] The difference between this comparative example and Example 1 is that the particle size of the silica powder after the hydrophobic treatment in Step S2 is 110 nm, and the other steps are the same as those in Example 1.
[0097] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 105.3°, the sliding angle is 4.3°, and the durability is 95.13°.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the thickness of the silica layer formed in Step S3 is 0.5 μm, and the other steps are the same as those in Example 1.
[0100] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 100.3°, the sliding angle is 5.3°, and the durability is 90.5°.
[0101] Comparative Example 4
[0102] The difference between this comparative example and Example 1 is that the thickness of the silica layer formed in Step S3 is 7 μm, and the other steps are the same as those in Example 1.
[0103] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 102.5°, the sliding angle is 4.7°, and the durability is 92.6°.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that the viscosity of the lubricating oil in Step S4 is 180 CS, and the other steps are the same as those in Example 1.
[0106] After testing, the contact angle of the finally sugar-hydrophobic modified stainless steel surface is 104.28°, the sliding angle is 4.6°, and the durability is 93.9°.
[0107] Comparative Example 6
[0108] The difference between this comparative example and Example 1 is that the viscosity of the lubricating oil in step S4 is 30 CS, and the remaining steps are the same as those in Example 1.
[0109] After testing, the contact angle of the stainless-steel surface after saccharide-modification is 104.1°, the sliding angle is 4.3°, and the durability is 94.25°.
[0110] Comparative Example 7
[0111] The difference between this comparative example and Example 1 is that polytetrafluoroethylene (PTFE), silicone oil coating, and ceramic coating in the prior art are adopted.
[0112] After testing, the contact angle of the polytetrafluoroethylene (PTFE) coating is 112°, the sliding angle is 4.5°, and the durability is 90.2°;
[0113] After testing, the contact angle of the silicone oil coating is 107°, the sliding angle is 4.8°, and the durability is 91.6°;
[0114] After testing, the contact angle of the ceramic coating is 116°, the sliding angle is 17°, and the durability is 107.6°.
[0115] The embodiments of the present invention have been described above. However, the present invention is not limited to the above specific embodiments. The above specific embodiments are merely illustrative rather than restrictive. Under the inspiration of the present invention, those of ordinary skill in the art can also make many forms without departing from the spirit and scope protected by the present invention and the claims, and all of them fall within the protection scope of the present invention.
Claims
1. A processing method for a sugar-phobic metal surface, characterized in that, It includes the following steps: Process the metal surface to form a rough surface; Hydrophobically treat the silica powder; Spray the hydrophobically treated silica powder onto the metal surface to form a silica layer; Coat lubricating oil on the surface of the silica layer to form a lubricating oil layer, and the processing is completed.
2. The processing method of the sugar-free metal surface according to claim 1, characterized in that The viscosity of the lubricating oil is 50 CS - 150 CS.
3. The processing method of the sugar-eliminating metal surface according to claim 2, wherein The viscosity of the lubricating oil is 100 CS.
4. The processing method of the sugar-eliminating metal surface according to claim 1, wherein, The particle size of the silica powder is greater than or equal to 10 nm and less than or equal to 100 nm.
5. The processing method of the sugar-free metal surface according to claim 6, characterized in that, The particle size of the silica powder is 30 nm.
6. The processing method of the sugar-free metal surface according to claim 1, characterized in that, The thickness of the silica layer is greater than or equal to 1 μm and less than or equal to 5 μm.
7. The processing method of the sugar-eliminating metal surface according to claim 6, characterized in that, The thickness of the silica layer is 2 μm.
8. The processing method of the sugar-free metal surface according to claim 1, wherein The lubricating oil is 3H food-grade dimethyl silicone oil or food-grade PFPE lubricating oil or food-grade vegetable oil or food-grade synthetic ester lubricating oil or food-grade white mineral oil.
9. The processing method of the metal surface with low sugar according to claim 1, characterized in that For the step of processing the metal surface to form a rough surface, a laser is used for processing. After the processing is completed, the sample is soaked in a mixed solution of hydrochloric acid and oxalic acid to remove the carbonized layer.
10. The processing method of the sugar-eliminating metal surface according to claim 1, wherein, The step of processing the metal surface to form a rough surface is realized by laser processing; the power of the laser is 500 mW - 1 W, the scanning speed is 2 mm / s - 5 mm / s; the scanning line spacing is 100 μm - 200 μm.